Regulation of Na+, K+ -ATPASE by D1-like dopamine receptors in the osmoregulatory gills of the blue crab, callinectes sapidus - Arnaldo, Francis Borromeo; Arnaldo, Francis Borromeo (Quezon City Marine Science Institute, College of Science, University of the Philippines Diliman, 2008)
The objective of the study was to test the hypothesis that D1-like receptors are expressed and act to increase cAMP production and decrease Na+,K+ -ATPase activity in the posterior gills of the euryhaline crab, Cailinectes sapidus.
Thesis (M.S. Marine Science)--University of the Philippines Diliman
Keywords: Blue crab fisheries